Phrasal Verbs Found in “Aquaman” Movie Subtitle and Their Translation into Indonesian - Ningrat, Ni Kadek Dwi Pradnya; Ngurah Parthama, I Gusti; Udayana, I Nyoman (Udayana Journal of Social Sciences and Humanities; Vol 8 No 1 (2024): Vol 8 No 1 (2024): UJoSSH, Februari 2024, 2024)
The title of this study is Phrasal Verbs Found in “Aquaman” Movie Subtitle and Their Translation into Indonesian. This study has two aims namely to analyze the types of translation procedure applied in the translation of English phrasal verbs in Aquaman movie subtitle into Indonesian subtitle and to analyze the translation equivalence of English phrasal verbs into Indonesian in Aquaman movie’s subtitle applying the theory of translation procedures by Vinay and Darbelnet and theory of translation equivalence by Nida. The English and Indonesian subtitle of Aquaman movie is the source of data in this study. The data was collected by using the documentation method. Descriptive and qualitative method is used to analyze the data. The findings show that there are three procedures applied in the subtitle. There are literal, transposition, modulation translation procedure. The translation equivalence that are found are the two equivalence which are formal and dynamic equivalence.